Prevalence and Risk Factors of Lungworm Infection in Small Ruminants in Selected Districts of Wolaita Zone, Southern Ethiopia - Wondimu Tessema; Minale Getachew; Ephrem Tora (Journal of Parasitology Research)
Among small ruminants, lungworms are important parasitic nematodes that infect the lower respiratory tract and are implicated in a high mortality and morbidity rate. However, the magnitude and its determinants of lungworm infection in the study districts are not known. The objective of this study was to estimate the prevalence of lungworm infection and assess associated risk factors in selected districts, Wolaita Zone, southern Ethiopia. A total of 742 fecal samples collected from 443 sheep and 299 goats were examined, using modified Baermann techniques, to recover first-stage larvae from fecal samples. Lungworms were detected in 271 (36.52%) samples infecting 192 (43.34%) sheep and 79 (26.42%) goats, respectively. Lungworm species Dictyocaulus filaria, Protostrongylus rufescens, and Muellerius capillaris were recovered in 114 (15.36%), 68 (9.16%), and 57 (7.68%) fecal samples, respectively. Mixed infection by two or more above species was noted in 32 (4.31%) of the samples. Among the determinants examined, agroecological environment, management system, and season showed statistically significant differences (p<0.05) with the prevalence of infection in small ruminants. On the other hand, lungworm infection among sexes, age groups, and body condition scores showed no statistically significant difference (p>0.05). The present study indicated that lungworm infection was a problem for sheep and goats in this study area. Thus, measures like deworming, early treatment, and improving animal husbandry should be practiced.